PENGENDALIAN PERSEDIAAN SUKU CADANG MAINTENANCE DI PT ABC DENGAN METODE EOQ - Pakpahan, Sopian; Sirait, Ganda (Computer Science and Industrial Engineering, 2022)
PT ABC is a manufacturing company engaged in the manufacture of lighting products and detection devices. This research was conducted in the maintenance department to support the lamp testing production process which focuses on the availability of critical maintenance spare parts. In this study only focuses on two types of spare parts, namely IC (integrated circuit) and IGBT (insulated gate bipolar transistor). Because they often run out of stock before the ordered orders arrive, because there is no set minimum stock order, and procurement costs tend to be high. The purpose of this study is to determine the amount of safety stock, to determine the reorder point and to determine inventory control can achieve efficiency and can minimize inventory costs by applying the EOQ method. After applying the EOQ method, the number of safety stock on IC spare parts is 51 pieces, reorder points are 102 pieces and the procurement cost is Rp.527.345 compared to the company's method is Rp.3.351.828 by using the EOQ method it can save costs of Rp.2.824 483. Safety stock on IGBT spare parts is 3 pieces, reorder point 6 pieces. And procurement costs are Rp.1.097.571 compared to the company's method of Rp.5.942.656 by using the EOQ method to save costs of Rp.4.845.085.